Jerantut District and Land Office practical training report / Nur Izzati Ibrahim - Ibrahim, Nur Izzati (2016)
Every state in the country is divided into several areas called Regions. The area is the implementation of development projects. Actually the projects planned in the center, but its implementation is at district level. An area will be governed by a chief known as District Officer. Jerantut District and Land Office is the main office at the district level Jerantut. In the district administration is also divided into three stages, the first stage is the Regional Administration which represent the administration, Mukim Administration and lastly the Village Development and Security Committee (JKKK). District officials also act as the secretariat to the Committee on Regional Development and Regional Planning Committee. Both committees will be chaired by the head of the administration itself which Jerantut District Officer. In the area will also be broken down into several smaller areas called Reuters. Administrative management in each county will be headed by a civil servant who was named Chief. This is a task ‘Penghulu’ help the District Office and other government agencies to implement development programs and development projects. His job also involves coordination of construction work at the village level. At the administrative level, lowest in the district administration is the village level. Some villagers will join and eventually became parishes. These villages will be led by someone who is known as the village head. The village head appointed by the state government and they should be responsible for all matters that are present in the village. They usually act through the Village Development and Security Committee (JKKK) to assist the district administration in implementing development projects.